2014
DOI: 10.1186/1741-7015-12-76
|View full text |Cite
|
Sign up to set email alerts
|

Additive effects of blood glucose lowering drugs, statins and renin-angiotensin system blockers on all-site cancer risk in patients with type 2 diabetes

Abstract: BackgroundHyperglycemia is associated with increased risk of all-site cancer that may be mediated through activation of the renin-angiotensin-system (RAS) and 3-hydroxy-3-methyl-glutaryl-coenzyme-A-reductase (HMGCR) pathways. We examined the joint associations of optimal glycemic control (HbA1c <7%), RAS inhibitors and HMGCR inhibitors on cancer incidence in patients with type 2 diabetes.MethodsPatients with type 2 diabetes, with or without a history of cancer or prior exposure to RAS or HMGCR inhibitors at ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 37 publications
0
21
1
Order By: Relevance
“…Previous studies showed that sleep duration in diabetic people had a U‐shaped relationship with glucose intolerance represented by hemoglobin A1c and homeostasis model assessment of insulin resistance, metabolic syndrome and levels of lipid, which are well known risk factors of cardiovascular disease. In addition, diabetic people with uncontrolled glycemia are shown to have higher risks of the incidence of cancer, the promotion of cancer growth, and the aggregation of infection than those with controlled glycemia . Nevertheless, in this study, we did not find any significant associations of ≤5 h or ≥9 h sleep with mortality except that listed above.…”
Section: Discussioncontrasting
confidence: 79%
“…Previous studies showed that sleep duration in diabetic people had a U‐shaped relationship with glucose intolerance represented by hemoglobin A1c and homeostasis model assessment of insulin resistance, metabolic syndrome and levels of lipid, which are well known risk factors of cardiovascular disease. In addition, diabetic people with uncontrolled glycemia are shown to have higher risks of the incidence of cancer, the promotion of cancer growth, and the aggregation of infection than those with controlled glycemia . Nevertheless, in this study, we did not find any significant associations of ≤5 h or ≥9 h sleep with mortality except that listed above.…”
Section: Discussioncontrasting
confidence: 79%
“…However, statins exhibit umpteen pleiotropic cholesterol independent effects including anti-oxidants by reducing superoxide formation (Uekawa et al, 2014), anti-inflammatory by reducing macrophage migration , anti-microbial effect in staphylococcus blood infections (López-Cortés et al, 2013), modulation of the neurotrophic levels (Wu et al, 2008) and up-regulation of L-type Ca 2+ channel affecting smooth muscle contraction (Clunn et al, 2010). Due to these multiple activities, preclinical studies have suggested the potential beneficial role of statins in a number of other diseased states like cancer (Khurana et al, 2007;Kong et al, 2014;Mondul et al, 2011), arthritis (Gottschalk et al, 2014), chronic obstructive pulmonary disease (Criner et al, 2014), Alzheimer's disease and Parkinson's disease (Barone et al, 2014;Wolozin et al, 2007) and chronic kidney disease (Dasari et al, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…We tested various combinations of exclusion/inclusion of immortal time and adjustment for drug indications at baseline or at the end of immortal time when drug was commenced Consistently, timedependent drug-exposure Cox models severely inflated the HR of these two drugs for CVD risk [5,6] , despite their proven cardioprotective effects in RCTs. In the statin-CVD validation [6] , compared to a HR of 0.63 (95%CI: 0.48 to 0.83) in a RCT [21] , exclusion of immortal time and adjustment for estimated covariables at the end of the immortal time when statins were commenced, resulted in a 52.3% inflation in the HR of statins for CVD (0.96, 0.72 to 1.27), which was above the higher bound of the 95%CI. On the other hand, inclusion of immortal time, i.e., ignoring immortal time bias, and adjustment for covariables at baseline generated the least inflated HR of 0.64 (0.48 to 0.84) which was within the HR estimates in clinical trial and inflated by 1.59% compared to the absolute HR of 0.63.…”
Section: Immortal Time and Immortal Time Biasmentioning
confidence: 99%
“…In order to test the validity of these methods [3,4] , we used a referent drug with proven benefits [e.g., statin or renin angiotensin system (RAS) inhibitors] and applied the methods to the Hong Kong Diabetes Registry [5,6] to find out if the estimated effect size fell within the bounds of that reported in RCTs with regard to their associations with CVD. We tested various combinations of exclusion/inclusion of immortal time and adjustment for drug indications at baseline or at the end of immortal time when drug was commenced Consistently, timedependent drug-exposure Cox models severely inflated the HR of these two drugs for CVD risk [5,6] , despite their proven cardioprotective effects in RCTs.…”
Section: Immortal Time and Immortal Time Biasmentioning
confidence: 99%
See 1 more Smart Citation